2018
DOI: 10.1186/s12917-018-1555-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new bovine viral diarrhea virus subtype in the Republic of Korea

Abstract: BackgroundBovine viral diarrhea virus (BVDV) is prevalent in Korean indigenous cattle, leading to substantial economic losses. This study was conducted to investigate the occurrence of BVDV. In 2016, a total of 143 blood samples were collected from asymptomatic Korean indigenous calves younger than 3-months of age from six different farms in the Republic of Korea (ROK).ResultsEighty-seven calves (60.8%, 87/143) were tested positive for BVDV as evaluated by RT-PCR analysis. Phylogenetic analysis based on the 5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Cattle are the natural host for BVDV (Walz et al ., 2010) and infections with the virus are endemic in cattle populations in many different parts of the world (Chernick and van der Meer, 2017; Velasova et al ., 2017; Yesilbag et al ., 2017; Aragaw et al ., 2018; Han et al ., 2018; Scharnbock et al ., 2018). The prevalence of BVDV infection based on serological surveys in different geographic regions range from 40 to 90% in individual cattle and 28–66% in cattle herds, while 0.5–2.5% of cattle were persistently infected (PI) with the virus (Walz et al ., 2010; Velasova et al ., 2017; Scharnbock et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cattle are the natural host for BVDV (Walz et al ., 2010) and infections with the virus are endemic in cattle populations in many different parts of the world (Chernick and van der Meer, 2017; Velasova et al ., 2017; Yesilbag et al ., 2017; Aragaw et al ., 2018; Han et al ., 2018; Scharnbock et al ., 2018). The prevalence of BVDV infection based on serological surveys in different geographic regions range from 40 to 90% in individual cattle and 28–66% in cattle herds, while 0.5–2.5% of cattle were persistently infected (PI) with the virus (Walz et al ., 2010; Velasova et al ., 2017; Scharnbock et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported BVDV infection in goats in the ROK [15, 16], and little is known about BVDV circulation and transmission in goat farms. Recently, we found that BVDV-1b is the predominant subtype circulating among Korean indigenous cattle [17]. Therefore, here, we aimed to investigate whether BVDV-1b infection can be established in Korean native goats via intranasal (IN) inoculation, evaluate the circulation of BVDV between cattle and Korean native goats, and characterize the outcome of BVDV infection in Korean native goats.…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, BVDV infection was detected in 98.7% of nonvaccinated herds (Cowley et al 2012). In addition, BVDV-1b and BVDV-1e were the most prevalent subtypes circulating in Italy, whereas the BVDV-1a and BVDV-2a subtypes were predominant and widespread in Korea (Bazzucchi et al 2017;Han et al 2018). The prevalence of persistently infected cattle from selected, nonrandom sample in six large South African feedlots was 2.9% (Meiring et al 2011), while prevalence of PI calves in Japan in a dairy herd was estimated about 7.0%, which was very high ratio compared to that in previous reports (Helal et al 2012).…”
Section: Introductionmentioning
confidence: 99%